2019
DOI: 10.4067/s0718-07642019000600301
|View full text |Cite
|
Sign up to set email alerts
|

Diseño, Implementación y Evaluación del Programa Transversal de Alfabetización Académica Lector-es

Abstract: Autor a quien deba ser dirigida la correspondencia ResumenEste artículo describe el diseño, implementación y evaluación del programa transversal de alfabetización académica Lector-es en estudiantes de formación inicial docente en la modalidad de educación a distancia de la Licenciatura en Educación Básica, con énfasis en Matemáticas, Humanidades y Lengua Castellana. El estudio, realizado en la Universidad Pedagógica y Tecnológica de Colombia, presenta un enfoque mixto, de tipo investigación evaluativa sustenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Two scoping reviews were identified, one with the objective of exploring and describing methods and strategies to promote the development of academic literacy ( Klarare et al, 2022 ) and the other with the objective of completing a characterization of complex thinking in academic literacy and higher education ( Suarez-Brito et al, 2022 ). Five articles were found that addressed interventions, two of them focused on writing ( Olivier, 2019 ; Zashikhina, 2021 ), one aimed at academic writing in English ( Roux et al, 2018 ), one about a Center for Reading, Writing and Orality ( Soares Sito et al, 2019 ), and one research focusing on a program that was designed in such a way as to associate learning with the production and analysis of texts specific to the students’ field of study ( Urzúa-Martínez et al, 2021 ), and another article dealt with a cross-cutting program of academic literacy ( Pardo-Espejo and Villanueva-Roa, 2019 ). In contrast, an investigation was also identified, the objective of which focuses on recognizing poor black youth in rural communities as knowledge givers and knowledge takers or “epistemic contributors” ( Soares Sito, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two scoping reviews were identified, one with the objective of exploring and describing methods and strategies to promote the development of academic literacy ( Klarare et al, 2022 ) and the other with the objective of completing a characterization of complex thinking in academic literacy and higher education ( Suarez-Brito et al, 2022 ). Five articles were found that addressed interventions, two of them focused on writing ( Olivier, 2019 ; Zashikhina, 2021 ), one aimed at academic writing in English ( Roux et al, 2018 ), one about a Center for Reading, Writing and Orality ( Soares Sito et al, 2019 ), and one research focusing on a program that was designed in such a way as to associate learning with the production and analysis of texts specific to the students’ field of study ( Urzúa-Martínez et al, 2021 ), and another article dealt with a cross-cutting program of academic literacy ( Pardo-Espejo and Villanueva-Roa, 2019 ). In contrast, an investigation was also identified, the objective of which focuses on recognizing poor black youth in rural communities as knowledge givers and knowledge takers or “epistemic contributors” ( Soares Sito, 2018 ).…”
Section: Introductionmentioning
confidence: 99%